Protection for Sale: An Empirical Investigation: Comment - Eicher, Theo; Osang, Thomas (American Economic Review, 2002)
Do contributions levels matter endogenous protection or is the existence of a lobby sufficient? Are lobbies’ net benefits from protection identical to their contribution levels, or does the level of protection simply reflect contribution levels of supporters and opponents? We estimate the Influence Driven (Grossman and Helpman, 1994) and the Tariff Function (Findlay and Wellisz, 1982) models within a unified theoretical framework to examine the contrasting implications derived from these two prominent tariff formation models. We find strong evidence that protection is indeed for sale. The important new result is, however, that not only the existence of lobbies matters, but also the relative size of the sectoral pro and anti protection contributions. Using J tests to compare the power of the models directly, we cannot reject the null of correct specification of the Influence Driven model and find evidence of some misspecification in the Tariff Function model.